2019
DOI: 10.1186/s13014-019-1299-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional outcome after laryngeal cancer treatment

Abstract: Background The functional outcome after the treatment of laryngeal cancer is tightly related to the quality of life of affected patients. The aim of this study is to describe the long-term morbidity and functional outcomes associated with the different treatment modalities for laryngeal cancer. Methods Retrospective chart review of 477 patients undergoing curatively intended treatment for laryngeal cancer at our tertiary referral center from 2001 to 2014: Details on pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 29 publications
(24 reference statements)
2
42
0
Order By: Relevance
“…To further investigate the molecular mechanisms underlying the role of LUCAT1 in the tumorigenesis of LSCC, the ENCORI database ( ) was used. It was predicted that LUCAT1 directly bound with miR-493, a miRNA previously reported to inhibit tumorigenesis occurred in the 3′-UTR ( 29 , 30 ) ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 90%
“…To further investigate the molecular mechanisms underlying the role of LUCAT1 in the tumorigenesis of LSCC, the ENCORI database ( ) was used. It was predicted that LUCAT1 directly bound with miR-493, a miRNA previously reported to inhibit tumorigenesis occurred in the 3′-UTR ( 29 , 30 ) ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 90%
“…[10][11][12][13] In a review of 477 patients with laryngeal cancer-the majority with glottic and early-stage disease-adjuvant therapy was required in 69 of 118 patients (58.5%) following primary surgical resection with curative intent. 10 TLM was the most frequent primary surgical modality, with a median total of 60 Gy among patients undergoing PORT. The addition of adjuvant RT may significantly affect long-term morbidity, as delayed severe laryngeal complications necessitating tracheostomy placement, gastrostomy dependence, or salvage laryngectomy remain possible.…”
Section: Discussionmentioning
confidence: 99%
“…1 PORT adds significant treatment toxicities and negatively affects quality of life. 6,[10][11][12][13] The primary objective of our study was to identify the incidence of PORT following laser resection for early-stage glottic cancer and to identify factors associated with its use.…”
mentioning
confidence: 99%
“…Interestingly, five of the eight feeding-tube insertions occurred beyond five years after CRT, thus highlighting the long-term side effects of CRT on larynx functions [41]. In a retrospective chart review of 477 patients undergoing curatively intended treatment for LC, Anschuetz et al found a 5% rate of feeding-tube dependence at the last follow-up in patients receiving primary CRT [42]. TL can be offered to these patients after adequate patient information in order to restore oral feeding if they accept the loss of laryngeal voice and definitive tracheostoma.…”
Section: Total Laryngectomy As a Functional Surgical Proceduresmentioning
confidence: 99%